Modern business management tools in the context of digital media development - E. Yu. Kamchatova; M. V. Khayrulova; E. K. Zorin (Путеводитель предпринимателя, 2021)
In modern economic conditions, there is an active transformation of interaction between economic entities and consumers, which occurs through the involvement of new tools that cause the onset of the industrial revolution (Industry 4.0). The increase in the scope of the Internet and the expansion of the digital space largely provides an opportunity to conveniently obtain information about works, services, goods and their cost. In such a situation, when the diffusion of products, goods, works and services is more active, and the stage of life associated with sales is characterized by an increasingly short period, specialists in the field of sales activities are focused on involving new opportunities on the Internet in order to promote them as productively as possible. the article presents the key types of social media used as objects of marketing activity. The article analyzes information about the income of companies due to the placement of advertising messages in social networks, and also presents the characteristics of global social media that have a positive experience of penetration into the world market. The article reveals the main advantages of modern technologies of product promotion in the market and identifies the difficulties that arise in its implementation. The main purpose of this study is to identify a modern tool that provides businesses with the opportunity to carry out stable sales activities of manufactured goods and expand the sales market based on the involvement of digital technologies in this business process.